Electrodes for High‐𝜅 Molecular Crystal Antimony Trioxide Gate Dielectrics for 2D Electronics - Alok Ranjan; Lunjie Zeng; Eva Olsson (Advanced Electronic Materials)
Abstract Wafer‐scale deposition of high‐𝜅 gate dielectrics compatible with atomically thin van der Waals layered semiconductors (e.g., MoS2, WS2, WSe2) is urgently needed for practical applications of field effect transistors based on 2D materials. A study on a high‐𝜅 molecular crystal antimony trioxide (Sb2O3) gate dielectric examined the role of electrode material on dielectric degradation and breakdown. It is demonstrated that the thin films of Sb2O3 can be uniformly deposited on a wafer scale. The current–voltage (I–V) curves show tightly controlled distributions of both leakage current and breakdown voltage. Electrical measurements reveal that defects are generated gradually upon electrical stressing. The evaluation of degradation is based on charge trapping, stress‐induced leakage current, and dielectric breakdown measurements. The breakdown voltage distribution follows a tight monomodal Weibull distribution suggesting a high quality of the film. Comparing Ti and Au as gate electrodes, both the breakdown field and the tunnel current are affected by the choice of electrode material. Transmission electron microscopy reveals that the chemistry at the electrode/Sb2O3 interface plays an important role and that Ti scavenges oxygen from the Sb2O3, forming a defective oxide layer at the Ti/Sb2O3 interface. For the Au electrode, this interfacial reaction is completely absent, improving the dielectric performance.